Drug Utilization Pattern of Psychotropic Drugs Prescribed in a Psychiatry Outpatient Department of a Tertiary Care Hospital - Shirure Nikhil S; Hotwani Jitendra H; Rao Ankita A (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Psychiatric disorders are one of the major causes of morbidity. Although psychotropic drugs have made a remarkable impact on outcome of psychiatric disorders, their utilization in actual clinical practice needs continuous monitoring. The World Health Organization (WHO) has prescribed drug use indicators for evaluating rational prescribing. Aim: This study was undertaken at a tertiary care centre in western India to study the utilization pattern of psychotropic drugs. Methods: After approval from the ethics committee, an observational, cross-sectional study involving 400 patients was done. The drug utilization pattern of psychotropics based on WHO prescribing drug use indicators was analysed using descriptive statistics. Results: In 400 prescriptions, a total of 894 psychotropic drugs were prescribed. The average number of psychotropic drugs per prescription was 2.2 ± 1.03. 93.51% of the psychotropic drugs were prescribed by generic name. The utilization of psychotropic drugs from the National List of Essential Medicines (NLEM), India 2015 was 69.13%. Only 0.44% of the prescriptions contained psychotropic injectable drugs. Only 0.44% of the prescriptions contained psychotropic fixed dose combinations. In our drug utilization study, escitalopram among the antidepressants, olanzapine among antipsychotics, sodium valproate among mood stabilizers, lorazepam among sedative hypnotic drugs, and propranolol among miscellaneous psychotropics—were the most frequently prescribed drugs. Conclusions: In our study, newer drugs were being prescribed more frequently due to their better safety and tolerability profiles. In view of changing therapeutic modalities in psychiatric diseases, regular monitoring of prescription pattern will contribute towards rational pharmacotherapy.